Chromatin Remodeling BAF155 Subunit Regulates the Genesis of Basal Progenitors in Developing Cortex - Narayanan, Ramanathan; Pham, Linh; Kerimoglu, Cemil; Watanabe, Takashi; Castro Hernandez, Ricardo; Sokpor, Godwin; Ulmke, Pauline Antonie; Kiszka, Kamila A.; Tonchev, Anton B.; Rosenbusch, Joachim; Seong, Rho H.; Teichmann, Ulrike; et al. (iScience, 2018)
The abundance of basal progenitors (BPs), basal radial glia progenitors (bRGs) and basal intermediate progenitors (bIPs), in primate brain has been correlated to the high degree of cortical folding. Here we examined the role of BAF155, a subunit of the chromatin remodeling BAF complex, in generation of cortical progenitor heterogeneity. The conditional deletion of BAF155 led to diminished bIP pool and increased number of bRGs, due to delamination of apical RGs. We found that BAF155 is required for normal activity of neurogenic transcription factor PAX6, thus controlling the expression of genes that are involved in bIP specification, cell-cell interaction, and establishment of adherens junction. In a PAX6-dependent manner, BAF155 regulates the expression of the CDC42 effector protein CEP4, thereby controlling progenitor delamination. Furthermore, BAF155-dependent chromatin remodeling seems to exert a specific role in the genesis of BPs through the regulation of human RG-specific genes (such as Foxn4) that possibly acquired evolutionary significance. [Display omitted] •BAF155 potentiates PAX6 transcriptional activity•BAF155 and PAX6 co-regulate bIP genesis in developing cerebral cortex•BAF155 and PAX6 control bRG genesis through aRG delamination non-cell-autonomously•BAF155 suppresses the expression of human RG-specific genes in developing mouse cortex Neuroscience; Molecular Neuroscience; Developmental Neuroscience